The Common Sense Model of Self-Regulation: Meta-Analysis and Test of a Process Model. - Hagger, Martin S.; Koch, Severine; Chatzisarantis, Nikos L. D.; Orbell, Sheina (Psychological Bulletin, 2017)
According to the common-sense model of self-regulation, individuals form lay representations of illnesses that guide coping procedures to manage illness threat. We meta-analyzed studies adopting the model to (a) examine the intercorrelations among illness representation dimensions, coping strategies, and illness outcomes; (b) test the sufficiency of a process model in which relations between illness representations and outcomes were mediated by coping strategies; and (c) test effects of moderators on model relations. Studies adopting the common-sense model in chronic illness (k = 254) were subjected to random-effects meta-analysis. The pattern of zero-order corrected correlations among illness representation dimensions (identity, consequences, timeline, perceived control, illness coherence, emotional representations), coping strategies (avoidance, cognitive reappraisal, emotion venting, problem-focused generic, problem-focused specific, seeking social support), and illness outcomes (disease state, distress, well-being, physical, role, and social functioning) was consistent with previous analyses. Meta-analytic path analyses supported a process model that included direct effects of illness representations on outcomes and indirect effects mediated by coping. Emotional representations and perceived control were consistently related to illness-related and functional outcomes via, respectively, lower and greater employment of coping strategies to deal with symptoms or manage treatment. Representations signaling threat (consequences, identity) had specific positive and negative indirect effects on outcomes through problem- and emotion-focused coping strategies. There was little evidence of moderation of model effects by study design, illness type and context, and study quality. A revised process model is proposed to guide future research which includes effects of moderators, individual differences, and beliefs about coping and treatment.